(untitled) (2015)
In common frameworks for Governance of Information Technology -ITa fundamental principle is related to identify and meet the needs of stakeholders inside and outside organizations. However, these frameworks do not document procedures to support the implementation. Co-creation is an interesting strategy to capture such requirements, allowing to generate a shared vision of the units of a company. This paper proposes a method based on co-creation to execute the needs identification phase in IT governance process. Five components for determining strategies, types of profiles of stakeholders, resources required for the implementation and motivation mechanisms are detailed. By employing the method, a significant increase in the flow of contributions, as well as creating innovative strategies to meet the needs within an organization in the IT governance were evident.